2017
DOI: 10.1038/nature22381
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic corticostriatal activity biases social bonding in monogamous female prairie voles

Abstract: Summary paragraph Adult pair bonding involves dramatic changes in the perception and valuation of another individual1. One key change is that partners come to reliably activate the brain's reward system2-6, though the precise neural mechanisms by which partners become rewarding during sociosexual interactions leading to a bond remain unclear. Using a prairie vole model of social bonding7, we show how a functional circuit from medial prefrontal cortex (mPFC) to nucleus accumbens (NAcc) is dynamically modulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 54 publications
10
92
1
Order By: Relevance
“…For example, the development of partner preference in voles requires not only OT, but also dopaminergic signaling in the nucleus accumbens and opioid signaling in the dorsal striatum (Burkett, Spiegel, Inoue, Murphy, &Young, 2011; Numan & Young, 2016). It was recently demonstrated that medial prefrontal cortex modulation of nucleus accumbens activity is involved in the formation of the partner preference, and that activation of this circuit in a social context can bias preference toward a partner without mating (Amadei et al, 2017). Furthermore, in mice, the optogenetically induced release of OT in the ventral tegmental area not only increased pro-social behaviors, but also increased excitatory drive to dopamine neurons as part of reward specific responses (Hung et al, 2017).…”
Section: Promising Future Directionsmentioning
confidence: 99%
“…For example, the development of partner preference in voles requires not only OT, but also dopaminergic signaling in the nucleus accumbens and opioid signaling in the dorsal striatum (Burkett, Spiegel, Inoue, Murphy, &Young, 2011; Numan & Young, 2016). It was recently demonstrated that medial prefrontal cortex modulation of nucleus accumbens activity is involved in the formation of the partner preference, and that activation of this circuit in a social context can bias preference toward a partner without mating (Amadei et al, 2017). Furthermore, in mice, the optogenetically induced release of OT in the ventral tegmental area not only increased pro-social behaviors, but also increased excitatory drive to dopamine neurons as part of reward specific responses (Hung et al, 2017).…”
Section: Promising Future Directionsmentioning
confidence: 99%
“…the amygdala, ventral tegmental area, NAc) (Okuyama et al 2016; Wong et al 2016; Lin et al 2011; Hitti & Siegelbaum 2014; Yizhar et al 2011; E. Lee et al 2016; van Kerkhof et al 2013; Takahashi et al 2014; Wang et al 2011; Bicks et al 2015; Gunaydin et al 2014; Felix-Ortiz et al 2016; Amadei et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Since behavioral analysis during cohabitation reflected a high level of individual variation, we tested if functional connectivity had a relationship in the display of huddling, and affiliative behavior shown to be socially relevant in the prairie vole and that may influence pair bond induction and formation (Amadei et al, 2017), we assessed the relationship between baseline functional connectivity, i.e. before cohabitation, and huddling latencies during cohabitation in voles of both sexes (N=32).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, novel electrophysiologic and optogenetic techniques have been employed to demonstrate that the functional connectivity between the nucleus accumbens (NAcc) and the medial prefrontal cortex (mPFC) during initial cohabitation in female prairie voles modulates the affiliative behavior with their potential partner (Amadei et al, 2017), providing exciting data of the relevance of such corticostriatal interactions for social bonding. However, this approach does not allow the study of the interaction of multiple brain regions, i.e.…”
Section: Introductionmentioning
confidence: 99%